Corticosterone stress hormone responses in oil rehabilitated and non-rehabilitated little penguins. Issue 1 (15th December 2016) - Chilvers, B.L.; Finlayson, G.; Candy, E.J.; Sriram, A.; Morgan, K.J.; Cockrem, J.F.
Abstract: Whether oiled wildlife should be rehabilitated during an oil spill is internationally debated. Research on little penguins (LP, Eudyptula minor ) rehabilitated and released back into a cleaned environment after the New Zealand C/V Rena grounding oil spill in 2011 found the rehabilitation process was effective at treating and reversing the negative effects of oil-contamination on penguin post-release survival, productivity and diving behaviour. Here we investigated the acute corticosterone stress response of LPs to determine if responses of rehabilitated birds differed from those of "control" birds. Corticosterone responses of LPs two years after an oil spill did not differ between rehabilitated and non-rehabilitated penguins. These results show that the rehabilitation process for LP did not affect their long-term physiological responses to humans. This indicates that wildlife can be rehabilitated and returned to the wild with similar human tolerance levels to non-rehabilitated birds and an absence of habituation. Highlights: There are few studies on the success and effectiveness of oiled wildlife rehabilitation This research investigates the acute corticosterone stress response of oiled little penguins (LPs) And indicates the rehabilitation process for LP did not affect their long-term physiological responses to humans Showing wildlife can be rehabilitated and returned to the wild with similar human tolerance levels to wild birds